Pengaruh Religiusitas, Uang Saku Dan Status Sosial Ekonomi Orang Tua Terhadap Konsumsi Santri Ponpes Darul Arifin Jambi - Safitri, Leni; Mubyarto, Novi; -, Habriyanto (Jurnal Ilmiah Ekonomi Islam, 2024)
The purpose of this study was to identify the influence of faktor s of religiosity, pocket money, and socioeconomic status of parents on the consumption patterns of students at Darul Arifin Jambi Islamic Boarding Schoo both partially and simultaneously. The purpose of this research is to increase knowledge and insight in the field of consumption patterns, both for researchers and those who need the information. In this study, researchers tried to find solutions to the problems of students who stil have consumptive behavior. The type of research used in this study is descriptive quantitative research. The population in this study was the students of Darul Arifin Jambi Islamic Boarding School, which totaled 1,237 students. In this study, researchers used the Slovin formula obtained 166 people as samples. Data collection techniques are carried out through the use of questionnaires, documentation, and observation. The data analysis techniques used in this study include data quality tests, classica assumption tests, multiple linear regression, t tests, F tests, and coefficients of determination. The results of the regression test showed that the three independent variables had a significant influence on Consumption Patterns. The regression coefficients of Religiosity, Pocket Money, and Socioeconomic Status of Parents were 0.290, 0.132, and 0.202, respectively. Partia testing shows that individually, the three independent variables also have a significant influence on Consumption Patterns. Test F shows that simultaneously, the three independent variables together have a significant effect on Consumption Patterns. An Adjusted R2 value of 40.5% indicates that the independent variable can explain 40.5% of the variation in Consumption Patterns, while 59.5% is influenced by other variables outside the research model. This study concluded that religiosity, pocket money, and socioeconomic status of parents have a significant effect on the consumption patterns of students at Darul Arifin Jambi Islamic Boarding School. Jointly or simultaneously, these three variables influence consumption patterns, besides that in the sobe test it is known that pocket money acts as a mediator in the influence of socioeconomic status of parents on consumption patterns.